Avaliação da circunferência da cintura como variável preditora de risco coronariano em estudo de base populacional - Goncalves, Christine Pereira (2008)
INTRODUCTION: Coronary heart disease is one of the most prevalent disease in Brazil and it determines high morbidity and mortality rates. Simple and practical measure that can be used to the health professionals to detect subjects with high risk of coronary heart disease development can be important for its prevention and early diagnostic. In the last years, attention has been given to the rule of abdominal obesity in the development of chronic diseases, especially of the cardiovascular disease. In practice, direct assessment of fat amount is difficult. Therefore, waist circumference can be used as an anthropometric indicator of abdominal adiposity. OBJECTIVES: To evaluate the association between waist circumference and coronary risk factors; to analyze the WHO waist circumference cut-off point capacity to predict these risk factors; to determine the best waist circumference cut-off point to predict hypertension, diabetes, dyslipidemia and high coronary risk in the study sample. METHODS: This is a population-based, cross-sectional study carried out in Vitória city, with 1,662 subjects. Data collect was done using structured questionnaire. Anthropometric data, arterial blood pressure measurements and blood biochemistry data were also collected. Coronary risk was calculated using Framingham score. It was considerated high as it was greater than 20%. WHO waist circumference cut-off points were used as reference. Correlation analyzis, linear and logistic regression were carried out. ROC curve construction using the waist circumference as predictor variable for the coronary risk factors was done. The best waist circumference cut-off point was determined by the Youden index. RESULTS: 764 men and 898 women aged 25 to 64 years were studied. Correlation and regression analyses showed positive association between waist circumference and hypertension, diabetes, dyslipidemia or high coronary risk. In men, the waist circumference cut-off point recommended by WHO presented low or moderate sensitivity to detect the studied risk factors. In women, the perfomance of the point corresponding to 80 cm was moderate to good. Area under the ROC curve was greater than 0.5 for all risk factors. This shows that the waist circumference is able to identify hypertensive, dyslipidemic, diabetic and high coronary risk subjects. Data of this study suggest waist circumference cut-off points between 85 and 95 cm in men and between 76 and 90 cm in women to identify hypertension, dyslipidemia, diabetes and high coronary risk to be used in population with similar characteristics of this study. CONCLUSION: Waist circumference can be used as predictor of hypertension, dyslipidemia, diabetes and high coronary risk. Because it is a simple and practical measure and for it has easy interpretation, it is proposed that waist circumference can be used as a tool of epidemilogical vigilance for these outcomes.